EVALUASI PENERAPAN SISTEM AKUNTANSI AKRUAL: STUDI KASUS DI BADAN LAYANAN UMUM DAERAH RSUD KARDINAH KOTA TEGAL - Sari, Yeni Priatna; tika, Hetika; Mahmudah, Nurul (Politeknik Negeri Madiun, 2017)
This Research Â to explore the extent to which the development of the application of The Government Regulation No. 71/2010 which has been applied in the process of accounting at BLUD Kardinah Hospital Tegal City. Associated with the change of government accounting system from cash base to accrual base as stipulated by Government Regulation No. 71 Year 2010.This research methodology used is descriptive method with interpretive method and using primary data obtained by interview to head of Accounting Department of Kardinah General Hospital as well as stakeholders at Kardinah General Hospital. The results of this study show that Kardinah hospitals are ready and already implemented Accounting Standard based on accruals. Judging from some parameters such as the application of PP 71 Year 2010, the readiness of human resources, organizational commitment, communication, quality of accounting information system, financial reporting quality, infrastructure and consultant support on accrual basis implementation. It is hoped that despite being ready to implement SAP accrual basis, the management of Kardinah General Hospital as well as Tegal City Government can always improve the regulations at the technical level in responding to the regulatory changes regarding the application of accrual basis in accounting